2010
DOI: 10.1159/000314649
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Triacetate Dialyzer Reduces Platelet Loss during Continuous Veno-Venous Hemofiltration

Abstract: Thrombocytopenia is a common complication in patients receiving continuous veno-venous hemofiltration (CVVH) in the intensive care unit. The hemofilter itself plays an important role in the genesis of thrombocytopenia. The present study was undertaken to test whether there were differences in platelet loss and activation during CVVH with a polysulfone (PS) hemofilter or a cellulose triacetate (CTA) dialyzer. 96 patients with thrombocytopenia and acute kidney injury requiring CVVH were randomly assigned to four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…6,7 The use of circuit anticoagulation, a factor which has been historically associated with reduced rates of thrombocytopenia, could have contributed to a decreased occurrence in these trials. 10 In one retrospective analysis, a similar platelet decline around 35% was seen between days 1 and 7 in patients placed on CRRT for HIT. 1 The cause of the thrombocytopenia in patients on CRRT remains to be determined.…”
Section: Platelet Statisticsmentioning
confidence: 84%
See 3 more Smart Citations
“…6,7 The use of circuit anticoagulation, a factor which has been historically associated with reduced rates of thrombocytopenia, could have contributed to a decreased occurrence in these trials. 10 In one retrospective analysis, a similar platelet decline around 35% was seen between days 1 and 7 in patients placed on CRRT for HIT. 1 The cause of the thrombocytopenia in patients on CRRT remains to be determined.…”
Section: Platelet Statisticsmentioning
confidence: 84%
“…Patients with cellulose triacetate filters and those with CRRT circuit anticoagulation had significantly lower occurrence of thrombocytopenia. 10 These authors also identified a lower rate of platelet activation with the triacetate filter by monitoring the level of bound GP IIb/IIIa. While the literature is minimal, this data signifies not only the presence of a reduction in platelets in patients on CRRT, but the relation of specific CRRT attributes to the risk and degree of platelet loss.…”
Section: Platelet Statisticsmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent proteomic analyses of the material eluted from the membrane after clinical hemodialysis show that the proteins found on cellulose triacetate membranes are dominated by the more abundant plasma proteins like albumin and lipoproteins compared to the high levels of fibrinogen and ficolin-2 on polysulfone membranes [5]. These differences in plasma protein adsorption are likely associated with the lower level of platelet loss seen with cellulose triacetate membranes compared to polysulfone [6,7]. …”
Section: Introductionmentioning
confidence: 99%